Functional characterisation of small signalling peptides in the regulation of Arabidopsis thaliana development - Smith, Stephanie (2016)
Root architecture governs the uptake of water and nutrients from the soil and thus is essential for plant growth and survival. The control of lateral root branching is a crucial aspect of determining root architecture, and is a process largely controlled by the phytohormone auxin, which promotes lateral root organogenesis from founder cells within the vasculature and also subsequent lateral root elongation. A small posttranslationally modified peptide, CTERMINALLY ENCODED PEPTIDE1 (CEP1) is a bioactive 15-amino acid peptide cleaved from a larger precursor protein previously shown to negatively affect primary root elongation and lateral root branching in Arabidopsis thaliana. Within this thesis, genetic, biochemical and pharmacological approaches are used to demonstrate that another member of the CEP family, CEP5, reduces primary root length and negatively regulates lateral root branching in Arabidopsis thaliana with minor effects on aboveground architecture. CEP5 is also demonstrated to have an antagonistic relationship with auxin, with increased abundance of CEP5 leading to downstream stabilisation of the auxin signalling repressor AUXIN/INDOLE ACETIC ACID (AUX/IAA) proteins. Correspondingly, reduced abundance of CEP5 increases auxin responses, including enhanced lateral root progression. These studies suggest CEP5 regulates lateral root branching through attenuation of auxin responses.